Pengaruh Curah Hujan terhadap Kualitas Air Sungai Way Kuripan sebagai Sumber Air Baku Perusahaan Daerah Air Minum (PDAM) Way Rilau - Ismadi Raharjo; Iskandar Zulkarnain; Suprapto Suprapto (Jurusan Teknologi Pertanian, 2013)
So far almost 30% people need clean water of urban city in Bandar Lampung supplied by PDAM Way Rilau. There are about 12 sources of raw water consisting of surface water , ground water, and springs are treated by PDAM Way Rilau. One source of raw water is surface water from Way Kuripan processed in